Effects of burning of slash piles of Acacia spp. and Eucalyptus camaldulensis biomass on soil physicochemical properties within Western Cape riparian and terrestrial areas - Maubane, Johannes Tshepo (Stellenbosch : Stellenbosch University, 2016)
Thesis (MScConsEcol)--Stellenbosch University, 2016.